Analisis Minat Belajar Santri berdasarkan Faktor Sarana Prasarana, Profesionalisme Guru dan Disiplin Kerja Guru (Studi pada Dayah Tauthiatuth Thullab Putri Arongan Kabupaten Bireuen) - Isa, Muhammad; Yusuf, M.; Simahatie, Mai (Aceh Cooperative Care, 2024)
Research on 92 Dayah Tauthiatuth Thullab Putri students, Simpang Mamplam District, Bireuen Regency with the aim of analyzing learning interest related to Infrastructure, teacher professionalism and teacher work discipline. With quantitative methods, and processing techniques using multiple regression analysis. The data collection technique uses a closed questionnaire. And the results show that: (1) there is a positive and significant influence of all the factors analyzed, namely learning facilities, teacher professionalism and teacher work discipline on students' interest in learning. (2) Simultaneously, the factors of infrastructure, professionalism and teacher work discipline have an influence of 48.6% on increasing student interest in learning.